Trace Metal Requirements for Microbial Enzymes Involved in the Production and Consumption of Methane and Nitrous Oxide - Glass, Jennifer; Orphan, Victoria J. (Frontiers in Microbiology, 2012)
Fluxes of greenhouse gases to the atmosphere are heavily influenced by microbiological activity. Microbial enzymes involved in the production and consumption of greenhouse gases often contain metal cofactors. While extensive research has examined the influence of Fe bioavailability on microbial CO2 cycling, fewer studies have explored metal requirements for microbial production and consumption of the second- and third-most abundant greenhouse gasses, methane (CH4) and nitrous oxide (N2O). Here we review the current state of biochemical, physiological and environmental research on transition metal requirements for microbial CH4 and N2O cycling. Methanogenic Archaea require large amounts of Fe, Ni and Co (and some Mo/W and Zn). Low bioavailability of Fe, Ni and Co limits methanogenesis in pure and mixed cultures and environmental studies. Anaerobic methane oxidation by “ANME” Archaea likely occurs via reverse methanogenesis since ANME possess most of the enzymes in the methanogenic pathway. Aerobic CH4 oxidation uses Cu or Fe for the first step depending on Cu availability, and additional Fe, Cu and Mo for later steps. N2O production via classical anaerobic denitrification is primarily Fe-based, whereas aerobic pathways (nitrifier denitrification and archaeal ammonia oxidation) require Cu in addition to, or possibly in place of, Fe. Genes encoding the Cu-containing N¬2O reductase, the only known enzyme capable of microbial N2O conversion to N2, have only been found in classical denitrifiers. Accumulation of N2O due to low Cu has been observed in pure cultures and a lake ecosystem, but not in marine systems. Future research is needed on metalloenzymes involved in the newly-discovered pathway of N2O production by ammonia oxidizing Archaea, biological mechanisms for scavenging scarce metals, and possible links between metal bioavailability and greenhouse gas fluxes both in anaerobic environments where metals may be limiting due to sulfide-metal scavenging.